HYDROPHOBIC INTERACTION β -CYCLODEXTRIN -DRUG INCLUSION COMPLEX - CATALYTIC EFFECT OF Cu (II) . - S. SHUNMUGAKANI,; D.EASWARAMOORTHY, (International Journal of Pharma and Bio Sciences, 2016)
The effect of β-Cyclodextrin with copper (II) catalyst on the oxidation of glutamine (drug) by PMS in acetic acid -sodium acetate buffer medium at 308K by kinetics studied. The phase solubility analysis was conducted the solubility of drug and β-cyclodextrin with copper (II) aqueous solutions and for calculating the correspondent thermodynamic parameters: free energy of activation (ΔS0) and enthalpy of activation (ΔH0) obtained as positively and entropy of activation (ΔG0) as negatively. It provides inclusion complex of the guest (drug) inside the cavity of host (β-Cyclodextrin) due to this hydrophobic interaction was confirmed by UV-Visible absorption studies to determine the stability constant using a modified Benesi- Hildebrand equation. The stability constant values of glutamine are 87.57 L/mol. The limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.29 LM-1 and 0.90 LM-1 respectively. The method has been successfully applied to the determination of pharmaceutical formulation with good accuracy of drug delivery.